Implementasi Algoritme AEGIS untuk Payload Data Protokol MQTT dan CoAP pada Raspberry Pi 3 - Helmy Rafi Nawawi; Ari Kusyanti; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Raspberry Pi 3 is a device that can be used as a middleware. Middleware facilitates communication and information management between heterogeneous components. Based on previous research, there is a security gap in the data transmission system that exposes data packets to an unauthorized party. This problem can be solved with AEGIS algorithm. AEGIS algorithm is a method that guarantees confidentiality and authentication. AEGIS is suitable to be implemented in network communication because it protects packets during transmission. Based on research results, AEGIS algorithm was successfully implemented in MQTT and CoAP protocol's data payload. AEGIS when implemented on the researched system was tested with vector testing and was stated as valid. Time performance test is conducted on middleware systems that either used MQTT or CoAP protocol's, the testing process was time data samples with and without using the AEGIS algorithm. The average results indicated the time difference of a MQTT system that used MQTT system that used AEGIS and without AEGIS was 19.592 milliseconds. Meanwhile, the average of time difference of CoAP system that used AEGIS and without AEGIS was 28.141 milliseconds. The above mentioned results prove that the AEGIS algorithm is capable of securing data confidentiality and authentication on a Raspberry Pi 3.